(untitled) (Eurasian Research Bulletin, 2023)
This article aims to ensure the effectiveness of the tax-budget system in the new development strategy of our republic. Tax policy plays a very important role in the economic policy of any country. The tax policy is closely related to other economic policies of the state and influences them. Correct development of tax policy and determination of its strategic and tactical directions is a very urgent and complex process.